Male/female Differences in Radial Arm Water Maze Execution After Chronic Exposure to Noise - Fernández-Quezada, David; Moran-Torres, Diana; Luquin, Sonia; Ruvalcaba-Delgadillo, Yaveth; García-Estrada, Joaquín; Jáuregui-Huerta, Fernando (Noise & health, 2019)
Introduction: Noise is one of the main sources of discomfort in modern societies. It affects physiology, behavior, and cognition of exposed subjects. Although the effects of noise on cognition are well known, gender role in noise-cognition relationship remains controversial. Aim: We analyzed the effects of noise on the ability of male and female rats to execute the Radial Arm Water Maze (RAWM) paradigm. Materials and Methods: Male and female Wistar rats were exposed to noise for 3 weeks, and the cognitive effects were assessed at the end of the exposure. RAWM execution included a three-day training phase and a reversal-learning phase conducted on the fourth day. Escape latency, reference memory errors, and working memory errors were quantified and compared between exposed and non-exposed subjects. Results: We found that male rats were in general more affected by noise. Execution during the three-day learning phase evidenced that male exposed rats employed significantly more time to acquire the task than the non-exposed. On the other hand, the exposed females solved the paradigm in latencies similar to control rats. Both, males and females diminished their capacity to execute on the fourth day when re-learning abilities were tested. Conclusion: We conclude that male rats might be less tolerable to noise compared to female ones and that spatial learning may be a cognitive function comparably more vulnerable to noise.